Development and Application of Transcription Terminators for Polyhydroxylkanoates Production in Halophilic Halomonas bluephagenesis TD01 - Xu, Mengmeng; Chang, Yue; Zhang, Yuyan; Wang, Weizhe; Hong, Jingyi; Zhao, Jiping; Lu, Xiaoyun; Tan, Dan (Frontiers in Microbiology, 2022)
Halomonas bluephagenesis TD01 is one of the ideal chassis for low-cost industrial production based on “Next Generation Industrial Biotechnology,” yet the limited genetically regulatory parts such as transcriptional terminators, which are crucial for tuned regulations on gene expression, have hampered the engineering and applications of the strain. In this study, a series of intrinsic Rho-independent terminators were developed by either genome mining or rational design, and seven of them proved to exhibit higher efficiencies than the canonical strong T7 terminator, among which three terminators displayed high efficiencies over 90%. A preliminary modeling on the sequence-efficiency relationship of the terminators suggested that the poly U sequence regularity, the length and GC content of the stem, and the number and the size of hairpin loops remarkably affected the termination efficiency (TE). The rational and de novo designs of novel synthetic terminators based on the sequence-efficiency relationship and the “main contributor” engineering strategy proved to be effective, and fine-tuned polyhydroxylkanoates production was also achieved by the regulation of these native or synthetic terminators with different efficiencies. Furthermore, a perfectly positive correlation between the promoter activity and the TE was revealed in our study. The study enriches our knowledge of transcriptional termination via its sequence–strength relationship and enables the precise regulation of gene expression and PHA synthesis by intrinsic terminators, contributing to the extensive applications of H. bluephagenesis TD01 in the low-cost production of various chemicals.